Designing Size and Stack Number of Fuel Cell Urban Vehicle - Nazwa, Intan; Satria, Dhimas; Jannah, Miftahul; Listijorini, Erny; Setiawan, Ipick; Pinem, Mekro Permana; Suprayogi, Dedy Triawan; Kanani, Nufus; Demustila, Harly (Universitas Sultan Ageng Tirtayasa, 2024)
A fuel cell converts the energy in the chemical reaction of a continuously supplied fuel and its oxidizing agent into electrical energy. Fuel cells are used in various industries, including the automotive industry. In this context, fuel cell electric vehicles (FCEVs) have emerged as a promising alternative that offers zero emissions and competitive performance. This work was conducted to obtain a fuel cell design and determine the fuel cell modeling that suits the needs of FCEVs. The Pahl and Beitz method with QFD is used. It was found that the type of fuel cell used is PEMFC (Proton Exchange Membrane Fuel Cell) with platinum electrode material, and the fuel used is hydrogen on a small scale. Overall, fuel cell dimensions were 175 x 259 x 175 mm, and the number of fuel cell stacks that can be arranged is 35. With this geometry, the factor of safety value obtained at the stack fuel cell is 26, and at the end plate fuel cell 2.4, this value indicates that the PEMFC design is safe. Then, the output voltage is 50.55 V, and the output current is 25.27 A, so the power generated is 1.277 kW.